4-REGULAR GRAPH OF DIAMETER 2 - Đỗ Như An; Nguyễn Đình Ái (Tạp chí Khoa học Đại học Đà Lạt)
A regular graph is a graph where each vertex has the same degree. A regular graph with vertices of degree k is called a k -regular graph or regular graph of degree k. Let G be a graph, the distance between two vertices in G is the number of edges in a shortest path connecting them. The diameter of G is the greatest distance between any pair of vertices. Let n4 be maximum integer number so that there exists an 4-regular graph on n4 vertices of diameter 2. We prove that n4 = 15.